Analisis Buku Bahasa Arab Tujuan Khusus: Bahasa Arab untuk Ekonomi dengan Standar 5C oleh The National Standards in Foreign Language Education Project - Fitra, Muh. Naufal; Wazkia, Hanif; Rosyidi, Abdul Wahab; Tamam, Muhammad Ibnu; Ilahi, Muhamad Muzaki Kurnia (Aksara: Jurnal Bahasa dan Sastra, 2024)
Arabic has an important role in global communication, including in the economic field. This is due to the rapid economic development of the Middle East which emphasizes the importance of mastering the Arabic language. One of the books that is a resource for learning Arabic for economic purposes is "Arabic Book for Special Purposes: Arabic for Economy" written by Dony Handriawan (2022) and published by Eureka Media Aksara. This study aims to analyze the quality of the book based on the 5C standard, identify aspects of the book that need to be strengthened based on the theory of the 5C standard, and provide recommendations to improve the quality of Arabic books for economic purposes. This research is literature research and uses content analysis techniques by paying attention to the instruments in the 5C standard. The results of this study show that the "Arabic Book for Special Purposes: Arabic for Economy" has met most of the standards in language teaching, especially in the aspects of communication, connections, comparisons, and communities. However, the book lacks emphasis on the cultures aspects of the Middle Eastern economy, which is an important area in learning Arabic for economic purposes. This lack of emphasis on the culture of the Middle Eastern economy is a gap between existing textbooks and international standards.Keywords: Arabic for Special Purposes, Arabic for Economic Purposes, Arabic Book Analysis, 5C Standards